Determinan Pertumbuhan Laba pada Perusahaan Industri Makanan dan Minuman Periode 2018-2022 - Anisa Yasmin Caniago; Kartika Hendra Titisari; Anita Wijayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Financial reports can be used as an instrument to assess company profit growth. Profit growth can be measured using financial and non-financial indicators. The researcher re-examined the debt to equity ratio, current ratio, total asset turnover, institutional ownership and independent board of commissioners on profit growth in food and beverage subsector companies listed on the Indonesian stock exchange. Quantitative research is defined as a systematic investigation of phenomena by collecting data that can be measured by performing statistical, mathematical or computational techniques. The population in this study are companies in the group of manufacturing companies listed on the Indonesian Stock Exchange (BEI) during the observation year 2018 - 2022. The sample in this study used a purposive sampling method. This research uses multiple linear analysis methods, testing independent variables is carried out on more than one variable. Data testing was carried out using SPSS and was carried out in stages. This research aims to test and analyze the influence of the variables debt to equity ratio, current ratio, total asset turnover, institutional ownership and independent board of commissioners on profit growth. The population used in this research is food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) for the 2018 - 2022 period.